If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -8 + 2 = 1 Reorder the terms: -8 + 2 + 2x = 1 Combine like terms: -8 + 2 = -6 -6 + 2x = 1 Solving -6 + 2x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 2x = 1 + 6 Combine like terms: -6 + 6 = 0 0 + 2x = 1 + 6 2x = 1 + 6 Combine like terms: 1 + 6 = 7 2x = 7 Divide each side by '2'. x = 3.5 Simplifying x = 3.5
| (x+11)2-11=0 | | -z+1=z-1 | | 0.13x-0.52=1.48x-3.523 | | X^6+8=0 | | (x+9)2-100=0 | | 3x-70=x | | 7x+5(1x+-1)=5+12x | | 7p-3=p+6 | | -5(t-2)+9t=6t-2 | | 4x+5y+7x+3y= | | (x-5)2-16=0 | | 3(4x-8)+1=12x-23 | | k+5=3-w | | 3x=-5y+4 | | -3+2=-10+3x | | 3.6+x=4.9 | | 8.21m=49.26 | | 4x+7=4(x+3) | | (x-2)2=144 | | -6(-7x-5)-2x=-1 | | 61+2x= | | 45+4x= | | -(1+7)-(-7-x)=36 | | -3(7+g)=9 | | 9114=93k | | 5(x-7)-3=-38 | | 3n+(12-5n)=22 | | 2/5-9=4 | | 4x^2-17x+25=3x+4 | | x=18.2-.4y | | (x+6)2=36 | | 6.5(-4)+4=-22 |